2022
DOI: 10.3390/su141710688
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Network Process-Based Sustainability Life Cycle Assessment of Concrete Bridges in Coastal Regions

Abstract: Since establishing the Sustainable Development Goals in 2015, the assessment of the sustainability performance of existing and future infrastructures has been in the spotlight of the scientific community. This is because the construction sector is essential for promoting the social welfare and economic development of countries, but is also one of the main environmental stressors existing to date. However, assessing infrastructure sustainability throughout its life cycle remains a significant challenge, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The second analysis stage employed the NPA to examine the priority strategies for organic paddy farming development. The key factors from the results of the first analysis stage were then analyzed using NPA [32] to determine the interactive dependence and correlation between each of the criteria used in solving complex problems through synthesis decomposition to produce the highest priority [33], as displayed in Figure 2. NPA utilizes the word cluster, each cluster having nodes that can communicate [34].…”
Section: Methodsmentioning
confidence: 99%
“…The second analysis stage employed the NPA to examine the priority strategies for organic paddy farming development. The key factors from the results of the first analysis stage were then analyzed using NPA [32] to determine the interactive dependence and correlation between each of the criteria used in solving complex problems through synthesis decomposition to produce the highest priority [33], as displayed in Figure 2. NPA utilizes the word cluster, each cluster having nodes that can communicate [34].…”
Section: Methodsmentioning
confidence: 99%
“…Each expert uses the consistency ratio (subjectively determined by each of them) to check the consistency of the network relationship between each level of interaction. The calculation process is as follows [21,22,40].…”
Section: Anp Methodsmentioning
confidence: 99%
“…Step 1.2: Selecting expert panel members Murry and Hammons [40] suggest that the appropriate number of experts for the Delphi method should be more than 10 and less than 30, primarily because a group of experts larger than 30 is likely to have different opinions, making it difficult to obtain valid conclusions.…”
Section: Stage 1: Constructing the Hierarchy Of Evaluationmentioning
confidence: 99%
“…MCDM facilitates the consideration of trade-offs between environmental impacts, economic costs, social benefits, and durability parameters, enabling a more balanced decision-making approach. Previous investigations have shown that MCDM methods can be successfully used in concrete materials [40][41][42][43][44][45][46]. For instance, Kurda et al [40] utilized a novel MCDM method to assess the overall sustainability of cementitious materials, validating this approach to analyze non-traditional materials in terms of mechanical properties, cost, environmental impact, and service life.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kurda et al [40] utilized a novel MCDM method to assess the overall sustainability of cementitious materials, validating this approach to analyze non-traditional materials in terms of mechanical properties, cost, environmental impact, and service life. Other studies employed standardized MCDM methods, such as Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), to select different alternatives in building construction, demonstrating the accuracy of these methods in selecting the best alternative [44,45]. However, the results are highly affected by the weighting scenarios, requiring an appropriate selection of these weights [47].…”
Section: Introductionmentioning
confidence: 99%